Circular Displacement Current Induced Anomalous Magneto‐Optical Effects in High Index Mie Resonators. Issue 8 (18th May 2022) - Xia, Shuang; Ignatyeva, Daria O.; Liu, Qing; Wang, Hanbin; Yang, Weihao; Qin, Jun; Chen, Yiqin; Duan, Huigao; Luo, Yi; Novák, Ondřej; Veis, Martin; Deng, Longjiang; et al.
Abstract: Dielectric Mie nanoresonators showing strong light–matter interaction at the nanoscale may enable new functionality in photonic devices, such as strong magneto‐optical effects. However, most reports so far have been focused on the enhancement of conventional magneto‐optical effects. Here, anomalous magneto‐optical effects are observed in high‐index‐contrast Si/Ce:YIG/YIG/SiO2 Mie resonators. In particular, giant modulation of light intensity in transverse magnetic configuration up to 6.4% under s‐polarized incidence appears, which is non‐existent in planar magneto‐optical thin films. A large rotation of transmitted light polarization in longitudinal magnetic configuration is also observed, which is two orders of magnitude higher than for planar magneto‐optical thin films. These phenomena are originated from the unique circular displacement current when exciting magnetic resonances in the Mie resonators, which change the electric field direction locally. This work indicates an uncharted territory of light polarization control based on complex modal profiles in all‐dielectric magneto‐optical Mie resonators and metasurfaces. Abstract : Employing high‐index‐contrast Si/Ce:YIG/YIG/SiO2 Mie nanoresonators, anomalous magneto‐optical effects are observed. Giant modulation of light intensity in transverse magnetic configuration under s‐polarized incidence appears, which is non‐existent in magneto‐optical thin films. In a 250 nm thick magneto‐optical layer, a giant s‐polarized TMOKE up to 6.4% is observed experimentally. These results indicate unprecedented opportunity to control light propagation with magnetization.